The malate synthase of Paracoccidioides brasiliensis is a linked surface protein that behaves as an anchorless adhesin - da Silva Neto, Benedito Rodrigues; da Silva, Julhiany de Fatima [UNESP]; Mendes-Giannini, Maria José Soares [UNESP]; Lenzi, Henrique Leonel; de Almeida Soares, Celia Maria; Pereira, Maristela (Biomed Central Ltd., 2009)
Background: The pathogenic fungus Paracoccidioides brasiliensis is the agent of paracoccidioidomycosis (PCM). This is a pulmonary mycosis acquired by inhalation of fungal airborne propagules that can disseminate to several organs and tissues leading to a severe form of the disease. Adhesion and invasion to host cells are essential steps involved in the internalization and dissemination of pathogens. Inside the host, P. brasiliensis may use the glyoxylate cycle for intracellular survival.Results: Here, we provide evidence that the malate synthase of P. brasiliensis (PbMLS) is located on the fungal cell surface, and is secreted. PbMLS was overexpressed in Escherichia coli, and polyclonal antibody was obtained against this protein. By using Confocal Laser Scanning Microscopy, PbMLS was detected in the cytoplasm and in the cell wall of the mother, but mainly of budding cells of the P. brasiliensis yeast phase. PbMLSr and its respective polyclonal antibody produced against this protein inhibited the interaction of P. brasiliensis with in vitro cultured epithelial cells A549.Conclusion: These observations indicated that cell wall-associated PbMLS could be mediating the binding of fungal cells to the host, thus contributing to the adhesion of fungus to host tissues and to the dissemination of infection, behaving as an anchorless adhesin.